Meanings of the polysemous Qur’ānic word Raḥmah (mercy) and its English translation - Hussein Fahim Abdalhussein,; Huda Falah Jawad, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The concept of polysemy, where a single word holds multiple meanings based on context, presents unique challenges in translating religious texts like the Holy Qur’ān. This study examines the meanings of the polysemous Qur’ānic word raḥmah (mercy) and its English translation in the Holy Qur’an. It identifies the contextual meanings of this Qur’ānic word in different Qur’ānic contexts and highlight the semantic differences among its meanings in various Qur’ānic contexts. Then, it examines how the semantic differences among the meanings of this word are reflected in the English translation by Abdullah Yusuf Ali. This study adopts the componential analysis proposed by Newmark for data analysis where the meaning of the source language word is compared with the meaning of the target language word i.e. its translation. The findings of the study reveal that raḥmah (mercy) is a polysemous word having ten meanings in various contexts in the Holy Qur’ān; these meanings include cordiality, Islam, paradise, rain, blessing, the Holy Qur’ān, livelihood and provision, victory, well-being and prophethood. However, the results show that this polysemous Qur’ānic word is literally translated as ‘mercy’ which does not reflect the intended meaning in the Qur’ānic verses. While previous studies have highlighted the literal translation of polysemous words in the Qur’ān, this study provides new insights by identifying specific contexts where literal translations fail to capture the deeper theological implications of 'raḥmah.' It proposes the use of targeted footnotes and parenthetical explanations as a practical solution for translators, offering a more accurate representation of the word’s nuanced meanings in different Qur’ānic contexts.